The Effect of Social Support on Student Academic Stress (Case Study Department of Economic Education Unima) - Siswanto, Sri Purwaningsih (Trigin Institute, 2023)
This study aims to determine whether there is an influence of social support on academic stress in students majoring in economic education . This research approach is a quantitative approach to the type of correlational research. The population in this study is whole student in majoring in economic education as much 1 023 . Research sample as much 21 3 coed students who taken using simple random sampling technique . The data collection tool uses a scale of social support adapted from Multidimensional Scale of Perceived Social Support (MSPSS) and academic stress scale adapted from Perceptions of Academic Stress (PAS) Scales . Data analysis technique using simple regression analysis. Based on the results of simple regression analysis, the coefficient value is obtained regression social support as big 0.067 2 _ with level significance as big 0.0 89 < 0.05. Besides That mark t count as big 2,062 > t table of 1.10 8 . Matter it can be concluded that variable X (social support) has an effect on variable Y (academic stress), which means there is influence positive support social to stress academic great student in the Department of Economic Education UNIMA.